Retrospective and modern aspects of the development of charity - Арабаджи, Наталя Борисівна; Арабаджи, Н. Б.; Арабаджи, Наталия Борисовна; Arabadzhy, Natalia B.; Корнієнко, Ірина Валеріївна; Корнієнко, І. В.; Корниенко, Ирина Валериевна; Korniienko, Iryna V. (Baltija Publishing, 2018)
The article considers the retrospective and modern aspects of the development of charitable activity in the socio-economic sense, which is the assistance to other persons at the expense of own welfare or free time, and provided that this assistance does not harm other persons and is carried out within the law. Charity should benefit not only the immediate recipient of benefit but also society as a whole. The authors emphasize that the conducted study supports their hypothesis that under the conditions of globalization, society increasingly focuses on social issues that arise as a result of insufficient state resources and so charity becomes a factor in their successful resolution. The development of charity is a system of social, economic, and cultural factors. One of the stages of the development of charity was the creation of charitable foundations specializing in various fields: scientific, cultural, sporting, educational projects, assistance to needy families, help for orphanages, hospitals, fundraising for expensive treatment and other projects. In today’s world, the attitude towards charity as a professional occupation has become widespread, becoming a “social norm.” Charitable funds are a separate and important component of the charitable institution. The concept of “charity” came into the public consciousness as a humanistic call of a person to go to the needy, regardless of religious, national, racial, social affiliation or political or ideological beliefs. Retrospective analysis showed that forms of philanthropy in the advanced form existed already in ancient Rome and ancient Greece; in medieval Europe, they already acquired the status of state and social policy at the legislative level. In the Christian aspect of ancient Rus of the adoption of the Orthodox faith in 988, the foundations of charity are laid as socio-ethical norms of society. In the second half of the XVIII century, as a result of secularization, charitable societies, hospitals, almshouses, open by public organizations and private individuals arise, that is, there are social and state institutions of charity. And charitable funds, which are socio-economic professional activities, are beginning to develop. From ancient to modern times, charitable activity is carried out in the forms of patronage, sponsorship, volunteering, fundraising. Modern trends of charity include: increase of the non-profit sector and its internationalization; cooperation of charitable foundations, development of a social partnership with business, state bodies, and foreign funds; professionalization through the creation of network charity. In turn, charity abroad is characterized by growing professionalism, a variety of forms and programs of cooperation, the growth and expansion of the sphere itself and its importance for non-profit, in particular, socio-cultural activities. The undisputed leader in this area is the USA – the birthplace of modern sponsorship and fundraising. The authors conditionally distinguish three levels of charity. The typology and general characteristics of foreign charitable foundations, typical for the USA, European countries, and Ukraine, are presented. Features of creation and functioning of quasi-public funds are considered. On a global scale, the foreign activity of the US foundations is significant, and the expenditures exceed the official foreign aid budgets of many countries. However, their presence in Ukraine is relatively low. The volume of support is negligible compared to official support amounts: according to the OECD, the amount of grants actually received by Ukraine from other states and multilateral donors in 2011–2017 amounted to more than 5 billion USD while less than 0.1 billion USD came to Ukraine from US foundations. But this does not exclude the role of private donors in solving certain problems, in particular, in terms of supporting civil society, protecting the rights of vulnerable groups of the population, etc.

У статті розглянуто ретроспективний та сучасний аспекти розвитку благодійної діяльності в соціально-економічному розумінні, яка полягає у наданні допомоги іншим особам за рахунок власного добробуту чи вільного часу, за умови, що ця допомога не завдає шкоди іншим особам та є здійснюється в рамках закону. Благодійність має приносити користь не лише безпосередньому одержувачу, а й суспільству в цілому. Автори наголошують, що проведене дослідження підтверджує їх гіпотезу про те, що в умовах глобалізації суспільство все більше зосереджується на соціальних проблемах, які виникають внаслідок недостатності державних ресурсів, і тому благодійність стає фактором їх успішного вирішення. Розвиток благодійності — це система соціальних, економічних і культурних чинників. Одним із етапів розвитку благодійності стало створення благодійних фондів, що спеціалізуються в різних сферах: наукові, культурні, спортивні, освітні проекти, допомога малозабезпеченим сім’ям, допомога дитячим будинкам, лікарням, збір коштів на дороге лікування та інші проекти. У сучасному світі ставлення до благодійності як до професійного заняття набуло поширення, ставши «соціальною нормою». Благодійні фонди є окремою і важливою складовою благодійної установи. Поняття «благодійність» увійшло у суспільну свідомість як гуманістичний заклик людини йти до нужденних, незалежно від релігійної, національної, расової, соціальної приналежності чи політичних чи ідеологічних переконань. Ретроспективний аналіз показав, що форми філантропії у розвинутій формі існували вже в Стародавньому Римі та Стародавній Греції; у середньовічній Європі вони вже на законодавчому рівні набули статусу державної та соціальної політики. У християнському аспекті давньої Русі прийняття православної віри в 988 р. закладаються основи милосердя як соціально-етичних норм суспільства. У другій половині XVIII століття в результаті секуляризації виникають благодійні товариства, лікарні, богадільні, відкриті громадськими організаціями та приватними особами, тобто виникають соціальні та державні установи благодійності. І починають розвиватися благодійні фонди, які є соціально-економічною професійною діяльністю. З найдавніших часів до сучасності благодійна діяльність здійснюється у формах меценатства, спонсорства, волонтерства, збору коштів. Сучасні тенденції благодійності: збільшення неприбуткового сектору та його інтернаціоналізація; співпраця благодійних фондів, розвиток соціального партнерства з бізнесом, державними органами, іноземними фондами; професіоналізація через створення мережевої благодійності. У свою чергу, благодійність за кордоном характеризується зростанням професіоналізму, різноманітністю форм і програм співпраці, зростанням і розширенням самої сфери та її значення для неприбуткової, зокрема, соціально-культурної діяльності. Беззаперечним лідером у цій сфері є США – батьківщина сучасного спонсорства та фандрейзингу. Автори умовно виділяють три рівні благодійності. Подано типологію та загальну характеристику зарубіжних благодійних фондів, характерних для США, країн Європи та України. Розглянуто особливості створення та функціонування квазідержавних фондів. У світовому масштабі зовнішня діяльність фондів США значна, а витрати перевищують офіційні бюджети зовнішньої допомоги багатьох країн. Проте їхня присутність в Україні відносно низька. Обсяг підтримки незначний порівняно з офіційними: за даними ОЕСР, обсяг грантів, фактично отриманих Україною від інших держав і багатосторонніх донорів у 2011–2017 рр., становив понад 5 млрд дол., тоді як надійшло менше 0,1 млрд дол. Україна від американських фондів. Але це не виключає ролі приватних донорів у вирішенні певних проблем, зокрема, в частині підтримки громадянського суспільства, захисту прав. уразливих груп населення тощо.
Arabadzhy N. Retrospective and modern aspects of the development of charity / N. Arabadzhy, I. Korniienko // Baltic Journal of Economic Studies. - Vol. 4. - № 5. - Baltija Publishing, 2018. - Р. 256-265.
Keywords: charity; evolution of charity; society; social policy; US charity; funds in Ukraine; благодійність; еволюція благодійності; суспільство; соціальна політика; благодійність США; фонди в Україні; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects